Magnetic Barkhausen Noise: Aspects of Generation and Modeling (The International Journal of Engineering & Information Technology (IJEIT), 2015)
The Magnetic Barkhausen noise (MBN) techniquemeasures discrete changes in magnetization, known as“Barkhausen jumps”, whi ch can be seen as steps i n the hysteresis curve. When a ferro-magnetic material issubjected to an external varying magnetic field, themagnetization of the material wil l change in a non-linearway. These changes in magnetization are described by thehysteresis curve and are the result of modifications of domain structure of the material. Changes in magnetizationare caused by domain wall creation, domain wallannihilation, domain wall motion and rotation. In order toimprove the interpretation of Barkhausen noise, models areneeded which describe the dependence of magnetization on material properties.